2019
DOI: 10.1038/s41380-018-0326-8
|View full text |Cite
|
Sign up to set email alerts
|

Significant shared heritability underlies suicide attempt and clinically predicted probability of attempting suicide

Abstract: Suicide accounts for nearly 800,000 deaths per year worldwide with rates of both deaths and attempts rising. Family studies have estimated substantial heritability of suicidal behavior; however, collecting the sample sizes necessary for successful genetic studies has remained a challenge. We utilized two different approaches in independent datasets to characterize the contribution of common genetic variation to suicide attempt. The first is a patient reported suicide attempt phenotype asked as part of an onlin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 40 publications
7
82
1
1
Order By: Relevance
“…Genetic studies have indicated that suicide attempt has a polygenic architecture, as polygenic risk scores for suicide attempt have shown modest predictive ability in independent samples and small but significant SNP-heritability estimates for suicide attempt have been reported (10,13). These findings are consistent with the presence of small genetic effects that the original GWAS were underpowered to detect at genome-wide significance.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Genetic studies have indicated that suicide attempt has a polygenic architecture, as polygenic risk scores for suicide attempt have shown modest predictive ability in independent samples and small but significant SNP-heritability estimates for suicide attempt have been reported (10,13). These findings are consistent with the presence of small genetic effects that the original GWAS were underpowered to detect at genome-wide significance.…”
Section: Introductionmentioning
confidence: 70%
“…These studies have failed to identify any replicable genetic associations, likely due to limited sample sizes that were underpowered to detect the genetic effects typical for a single SNP. Other GWAS have examined subjects recruited specifically on the basis of suicide attempt, or suicide attempters and non-attempters from population-based cohorts, but to date no loci have been robustly implicated (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Genotyping and QC of this sample have been described elsewhere. 20,33 PheWAS: A logistic regression model was fitted to each of 897 case/control phenotypes to estimate the odds of each diagnosis given the loneliness polygenic score, after adjustment for sex, median age across the EHR, top 10 principal components of ancestry, and genotyping batch. symptoms, and 52 injuries/poisonings.…”
Section: Ld-score Regression Heritability Partitioningmentioning
confidence: 99%
“…On balance, some studies indicate that bootstrap optimism correction methods perform similarly to other internal validation methods (73,74), random forest models can generalize well to new data (75,76), and random forest combined with bootstrap optimism correction performs similarly to other internal validation methods and other machine learning techniques (73,77,78). There is also evidence that Walsh et al's algorithm (64) using this approach generalizes well to new samples and new suicide-related outcomes (79,80). Nonetheless, much remains unknown about how various methods perform under various conditions, so at a minimum these discrepancies indicate that it would be prudent to conduct analyses with multiple internal validation techniques.…”
Section: Internal Validationmentioning
confidence: 99%